Asia and Pacific Small States Monitor, August 2014 - Boyce, Shari; Cabezon, Ezequiel; Dodzin, Sergei; Jamaludin, Fazurin (Washington, D.C. : International Monetary Fund, 2014)
This issue of the Asia and Pacific Small States Monitor focuses on the challenges facing Asia and Pacific small states associated with natural disasters and climate change. Most tourism-oriented economies experienced a robust increase in arrivals, partly reflecting country-specific factors. Among commodity exporters (Bhutan, Solomon Islands, and Timor-Leste) and other Asia and Pacific small states, growth remains uneven: robust activity in Bhutan was driven mainly by hydropower-related construction activities; Solomon Islands experienced a continuing decline of logging stocks and a short-term disruption of gold production; and Timor-Leste's ongoing depletion of oil reserves has led to a tighter budget constraint and lower government spending in the non-oil sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet